An Exploratory Study of Police Officers: Low Compassion Satisfaction and Compassion Fatigue - Grant, Heath Blair; Lavery, Cathryn F.; Decarlo, John (Frontiers in Psychology, 2019)
Background: Compassion fatigue, or the physical, mental, and emotional state experienced by professionals that assist others in distress, has been well documented in several caring professions such as nurses, firefighters, and emergency medical technicians. Until the current study, it has only rarely been examined in police samples despite their high rates of stress and suicide which is a likely result of a depletion of compassion satisfaction, or the pleasure an officer gets from relating to and helping others. Aim: This study documents findings from an ongoing study of compassion fatigue amongst a sample of US urban police officers which suggests the possibility of a future risk for high burnout. Conclusion: Very low levels of compassion fatigue were found in the sampled police officers in comparison to what would be expected from the general population. Where compassion fatigue was found in the sampled police, it was significantly correlated to the level of compassion satisfaction. A potential cause for concern is that the incidence of levels of reported compassion satisfaction were also low in the sample (in the bottom quartile compared to the general population). This suggests a possibility of higher numbers of burnout in the future given the role of compassion satisfaction as a buffer against compassion fatigue in policing.